KONSTRUKSI IJMA’ DALAM PERSPEKTIF MUHAMMADIYAH - Aisyah, Aisyah; Lisnawati, Lisnawati; Reza, Muhammad; Oktorisa, Tanti (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Ijma' is one of the complementary sources of law, in addition to the Quran and Hadith. Because, the two main sources of Islamic teaching, namely the Quran and Hadith alone are not enough to answer all the problems that exist in society, and are also supported by many differences of opinion among the mujtahid. In general ahkam, what is meant by nash here is only the Quran and Hadith. Ijma' is not part of the nash (ghair al-nash). This is based on the opinion that Ijma' is more of a process rather than a product. Muhammadiyah believes that Ijma' cannot be used as a primary source in religious teachings. This research is a qualitative writing, which refers to the library research method, with sources from other Islamic books and journals. Thus, the result of the analysis obtained is that Muhammadiyah does not make Ijma' as a source of basic law, but only positions it as a paractextual source